Classifying Insurance Reserve Period via Claim Frequency Domain Using Hawkes Process - Effendie, Adhitya Ronnie (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
In this paper, the insurance reserve period will be classified according to the claim frequency domain, such as high-or low-frequency periods. We use the clustering method to create and group claims data according to their frequency period. Meanwhile, we use a risk process to mimic and predict the movement of the reserve from time to time in each group of claim period that is formed. The risk process model used here is the Hawkes process, which is a one-dimensional simple point process and a special type of self-exciting process. Based on this process, we will estimate the reserve at a certain date in the future and the average historical reserve for each group period.